The Ability of a Cytomegalovirus ELISPOT Assay to Predict Outcome of Low-Level CMV Reactivation in Hematopoietic Cell Transplant Recipients. (6th October 2018) - El Haddad, Lynn; Ariza-Heredia, Ella; Shah, Dimpy P; Jiang, Ying; Blanchard, Ted; Ghantoji, Shashank S; El Chaer, Firas; El-Haddad, Danielle; Prayag, Amrita; Nesher, Lior; Rezvani, Katy; Shpall, Elizabeth; et al.
Abstract : Most patients with high CMV-CMI and low-level CMV reactivation did not progress to clinically significant CMV infection. Low CMV-CMI and steroids use were the only predictors for CMV progression from low-level reactivation. Abstract: Background: Cytomegalovirus (CMV) infections in hematopoietic cell transplant (HCT) recipients cause substantial morbidity and mortality. CMV cell-mediated immunity (CMV-CMI) can be determined by levels of interferon gamma (IFN-γ) production using an enzyme-linked immunospot (ELISPOT) CMV assay (T-SPOT.CMV assay). In this study, we evaluated the ability of this assay to predict the outcome of low-level CMV reactivation in HCT recipients. Methods: We followed 55 HCT recipients with low-level CMV reactivation up to 8 weeks from enrollment. Progression to clinically significant CMV infection (CS-CMVi) was defined as a CMV load >1000 IU/mL or > 500 IU/mL in patients receiving matched related/autologous or matched unrelated transplants, respectively, and initiation of antiviral treatment. Results: Progression to CS-CMVi occurred in 31 (56%) of the HCT recipients. Spot counts of CMV-specific pp65 and IE1 antigens were significantly lower in patients who had CS-CMVi than in patients who did not. On multivariate analysis, the ELISPOT CMV responses and steroids use were the only predictors of progression to CS-CMVi. Conclusions: A strong association between low CMV-CMI and progression to CS-CMVi was observed in HCT recipients. The implementation of serial monitoring of CMV-CMI may identify patients at risk of progression to CS-CMVi that require antiviral therapy.